Development of an animated infographic on Permanent Health Education - Letícia Lopes Dorneles; Vivian Do Prado Martins; Caroline Silva Morelato; Fernanda Dos Santos Nogueira De Goes; Luciana Mara Monti Fonseca; Rosangela Andrade Aukar De Camargo (Universidade de São Paulo, 2020)
Objective: to create an animated infographic on the concept of Permanent Health Education according to the National Policy and its main differences compared to continuing education and health education. Method: a methodological study that analyzed context and knowledge gaps with a literature review and brainstorming; synthesized knowledge into a concept map; built and validated a script; created a didactic design; and produced infographic media. 18 representatives from the Center for Permanent Education and Humanization participated in the stages of context analysis and synthesis of knowledge, and six specialists participated in the validation of the script. Results: through the combination of texts, images, audios, animations and transitions, the concepts, principles and legal journey of the Permanent Education policy were presented with examples from daily work and, at the end, the difference compared to continuing education and health education is presented. The specialist on the theme evaluated the infographic positively as it has clear information that meet the needs of the target audience; favors learning; and is able to circulate in the scientific environment. Conclusion: the infographic includes content on Permanent Health Education as it represents the daily work scenario and encourages reflection by the health care workers.